2020
DOI: 10.1111/mpp.12975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the cucumber mosaic virus 2a protein on aphid–plant interactions in Arabidopsis thaliana

Abstract: Cucumber mosaic virus (CMV) is an insect-transmitted virus that modifies interactions between its infected host plants and its aphid vectors in ways that increase the probability of transmission over various ranges and timescales (Donnelly et al., 2019; Carr et al., 2020). CMV does not infect its aphid vectors but influences their behaviour by altering the biochemistry of infected host plants. The paradigmatic example of this phenomenon is the interaction of the aphids Aphis gossypii and Myzus persicae with Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The results are also consistent with previous work showing that CMV and its 2b protein can inhibit induction of JA-mediated gene expression (Lewsey et al, 2010;Westwood et al, 2014;Wu et al, 2017). Sequences within the CMV 2a protein (Rhee et al, 2020) trigger the induction of both the mechanism that inhibits growth of M. persicae (which we have shown here to be BAK1-dependent), as well as the mechanism that inhibits reproduction of M. persicae and B. brassicae (which we have shown here to be BAK1-independent). Taken together, these results suggest that the 2a protein most likely interferes in some manner with JA-mediated signalling, and that this leads to induction of at least two mechanisms that inhibit aphid performance on A. thaliana.…”
Section: Previous Work On Interactions Between a Thaliana And B Brassicaesupporting
confidence: 92%
See 3 more Smart Citations
“…The results are also consistent with previous work showing that CMV and its 2b protein can inhibit induction of JA-mediated gene expression (Lewsey et al, 2010;Westwood et al, 2014;Wu et al, 2017). Sequences within the CMV 2a protein (Rhee et al, 2020) trigger the induction of both the mechanism that inhibits growth of M. persicae (which we have shown here to be BAK1-dependent), as well as the mechanism that inhibits reproduction of M. persicae and B. brassicae (which we have shown here to be BAK1-independent). Taken together, these results suggest that the 2a protein most likely interferes in some manner with JA-mediated signalling, and that this leads to induction of at least two mechanisms that inhibit aphid performance on A. thaliana.…”
Section: Previous Work On Interactions Between a Thaliana And B Brassicaesupporting
confidence: 92%
“…We recently showed that in A. thaliana the CMV 2a protein induces resistance not only to aphid growth but also to aphid reproduction (Rhee et al, 2020 ). Here, we confirmed that the fecundity of aphids placed on CMV‐infected plants was diminished compared to aphids placed on mock‐inoculated plants (Figure 2 and Spreadsheet S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some viruses, by altering plant metabolism, particularly by changing emission of VOCs or the accumulation of nutrients or distasteful compounds in plant tissue, can manipulate host-vector interactions in ways that favor their onward transmission ( Casteel et al, 2014 , 2015 ; Mauck et al, 2016 ; Groen et al, 2017 ; Carr et al, 2018 ; Donnelly et al, 2019 ). For example, CMV and potyviral gene products can affect plant VOC emission or accumulation of non-volatile metabolites to stimulate dispersal or settling of aphids on different plant hosts ( Lewsey et al, 2010 ; Ziebell et al, 2011 ; Westwood et al, 2013 ; Casteel et al, 2014 , 2015 ; Rhee et al, 2020 ; Tungadi et al, 2020 ). In squash and cucumber, infection with CMV increases emission of aphid-attracting VOCs while also causing accumulation of distasteful soluble compounds ( Mauck et al, 2010 ; Carmo-Sousa et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%